Send for me - Fox, Lauren (Alfred A. Knopf, 2021)
"From the author of the highly praised Days of Awe: a sweeping, achingly beautiful new novel that moves between Germany on the eve of World War II and present day Wisconsin, unspooling a story of love, longing, and the ceaseless push and pull of motherhood"--